Comparing the functional consequences of human stem cell transplantation in the irradiated rat brain - Acharya, Munjal M. (2012)
Radiotherapy is a frontline treatment for the clinical management of CNS tumors. Though effective in eradicating tumor cells, radiotherapy also depletes neural stem and progenitor cells in the hippocampus that are important for neurogenesis and cognitive function. Consequently, the use of radiation to control primary and metastatic brain tumors often leads to debilitating and progressive cognitive decrements in surviving patients, representing a serious medical condition that to date, has no satisfactory, long-term solutions. As a result, we have explored the use of stem cells as therapeutic agents to improve cognition after radiotherapy. Our past work has demonstrated the capability of cranially transplanted human embryonic (hESCs) and neural (hNSCs) stem cells to functionally restore cognition in rats 1 and 4-months after head-only irradiation. We have now expanded our cognitive analyses with hESCs and quantified both survival and differentiated fates of engrafted cells at 1 and 4 months after irradiation. Our findings indicate the capability of hESC transplantation to ameliorate radiation-induced cognitive dysfunction 1-month following cranial irradiation, using a hippocampal-dependent novel place recognition task. Irradiated animals not engrafted with stem cells experienced prolonged and significant cognitive dysfunction. Stereological estimates indicated that 35% and 17% of the transplanted hESCs survived at 1- and 4-months post-grafting, respectively. One month after irradiation and grafting, phenotypic analyses revealed that 26% and 31% of the hESCs differentiated into neurons and astrocytes, while at the 4-month time, neuronal and astrocytic differentiation was 7% and 46%, respectively. Comparisons between present and past data with hESCs and hNSCs demonstrates equivalent cognitive restoration and a preference of hNSCs to commit to neuronal versus astrocytic lineages over extended engraftment times. Our data demonstrate the functional utility of human stem cell replacement strategies for ameliorating the adverse effects of cranial irradiation on cognition.